RESSIGNIFICANDO THE TEACHING PRACTICE FOR YOUNG AND ADULTS EDUCATION BASED ON PARTICIPANT RESEARCH - Marcio Hoff (Editora da Universidade de Santa Cruz do Sul, 2008)
The objective of this document is make a brief report of the evolution of Young and Adults Education (EJA) in the historical-educational context of Brazil, over all from century XX till the 90 decade, with the writing of the new LDBEN- Guidelines and Bases National Education Law and the guidelines concerning to EJA, focusing the situation of this modality of education post-LDBEN, specially in relation to teachers's pedagogical formation. The text brings up the problematic of the necessity of permanent spaces of teachers continued formation of this modality and tells a practical experience of formation accomplished with teachers of the Education State System in the cities of Cidreira, Capivari and Palmares do Sul, of Rio Grande do Sul State. Approaching the participant research from the classroom, the meetings have happened from July to December, 2006, with UNESCO and Education State Secretaryship support according to UNISC - Universidade de Santa Cruz do Sul.